Gaya Komunikasi Orang Tua dalam Pengasuhan Generasi Alpha di BKB Mawar Larangan Kota Cirebon - Restu Puteri Sujiwo (Pancanaka, 2022)
The communication style of parents in parenting can affect the condition and character of the child even until the child grows into an adult. Parenting needs to be customized based on the growth and development of children, especially the alpha generation category which requires parents to focus on parenting so that children can grow well and optimally through effective communication styles. Therefore, this study was conducted to determine the communication style of parents in parenting as to what is done to alpha generation children through a qualitative descriptive approach. This study used purposive sampling with data collection techniques through interviews with group members in Bina Keluarga Balita Mawar RW 15 Larangan Village, Harjamukti District, Cirebon City, which was followed by three respondents. The analysis of the results of this study used a triangulation technique to compare interview and observation data. Researchers found that parents apply aggressive and assertive communication styles in parenting their children. In addition, in the implementation of communication styles in parenting, there are several obstacles experienced by parents, one of which is internal barriers, when parents are still unable to control their emotions in caring for their children.